The Utilization of Rice Sack Waste as a Substitute Material for Fiber in Fiber Tensile Strength - Mas Shobihatul Inaya; Meilinda Eka Fatmawati; Muhammad Akbar Febianto; Riska Dwi Apriliani; Denny Oktavina Radianto (Formosa Journal of Science and Technology, 2023)
This research was conducted with the aim of testing the mechanical properties of fiberglass composites made from normal fiberglass and a mixture of used rice sack waste. This research was conducted using two treatments, namely normal fiberglass and mixed fiberglass with waste. The method used is experimental with one repetition. The experimental results show that the tensile strength of lamina composites with polyester resin matrix and used rice sack fiber reinforcement is strongly influenced by fiber orientation. Therefore, mixed fiber specimens with a mixture of used rice sack fiber can be used as an alternative material to replace normal fiber.